THE ROLE OF QURANIC VERSES IN ENHANCING SOUL TRANQUILITY AND MENTAL HEALTH - Isdianto, Andik; Al Indunissy, Nuruddin; Fitrianti, Novariza (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study delves into the significant impact of Quranic verses on fostering mental and spiritual health, focusing particularly on enhancing soul tranquility through spiritual therapy. In the face of rising mental health issues such as stress, anxiety, and depression, incorporating spiritual dimensions within psychotherapy has proven to be essential. Utilizing a comprehensive literature review methodology, this research scrutinized various academic sources to evaluate the effectiveness of integrating Quranic verses in contemporary psychotherapy practices. The findings reveal that embedding spiritual elements notably promotes soul tranquility, reduces stress symptoms, and improves overall life quality. This underscores the Quran's pivotal role in supporting both psychological therapy and spiritual well-being, validating the verses' utility as therapeutic tools. The study suggests that future research should expand on the exploration of these spiritual practices in varied clinical settings to further confirm their benefits in enhancing mental health. The inclusion of spiritual values in clinical practice not only aids in mental health recovery but also meets modern therapeutic demands, providing a holistic approach to maintaining mental and soul tranquility.